Atuação do Ministério Público e da Agência Nacional de Saúde em face dos planos de saúde coletivos - Guimarães, Giovane Serra Azul (2009)
The theme of this work was chosen owing to its importance, since it is a crucial collective issue as it refers to health insurance contracts, which involve the fundamental rights pointed out in the provisions of Brazilian Constitution, being the only public service therein expressly defined. The central aim of the present dissertation is firstly to demonstrate that collective contracts of health insurance involve a consumption relationship and that they have social relevance, which establishes the special standing of prosecutors in defending consumer s diffuse, collective and homogenous individual interests, and secondly, to analyze the available means of defending consumers both in administrative and judicial proceedings. It is also intended to demonstrate that the Supplementary Health National Agency is responsible for inspecting all the aspects of the aforementioned health insurance plans, including price readjustment, in spite of the still existing controversies. In order to reach the outlined objectives, legislation, doctrine and previous judicial decisions were investigated, including a detailed study of the Brazilian Health Insurance Law